Development and usability testing of a web‐based self‐management intervention for oral cancer survivors and their family caregivers. (27th October 2015) - Badr, H.; Lipnick, D.; Diefenbach, M.A.; Posner, M.; Kotz, T.; Miles, B.; Genden, E.
Abstract : Oral cancer (OC) survivors experience debilitating side effects that affect their quality of life (QOL) and that of their caregivers. This study aimed to develop and evaluate a dyadic, web‐based intervention to improve survivor self‐management and survivor/caregiver QOL. A qualitative needs assessment (semi‐structured interviews) with 13 OC survivors and 12 caregivers was conducted to discern information and support needs as well as preferences regarding website features and tools. Results using Grounded Theory analysis showed that OC survivors and caregivers: (1) want and need practical advice about managing side effects; (2) want to reach out to other survivors/caregivers for information and support; and (3) have both overlapping and unique needs and preferences regarding website features. Usability testing ( N  = 6 survivors; 5 caregivers) uncovered problems with the intuitiveness, navigation and design of the website that were subsequently addressed. Users rated the website favourably on the dimensions of attractiveness, controllability, efficiency, intuitiveness and learnability, and gave it a total usability score of 80/100. Overall, this study demonstrates that OC survivors and caregivers are interested in using an online programme to improve QOL, and that providing tailored website content and features based on the person's role as survivor or caregiver is important in this population.